Contribution of thin-slice (1 mm) axial proton density MR images for identification and classification of meniscal tears: correlative study with arthroscopy - Gökalp, G (The British Institute of Radiology., 2012)
OBJECTIVE: To evaluate the diagnostic efficacy of thin-slice (1 mm) axial proton density-weighted (PDW) MRI of the knee for meniscal tear detection and classification. METHODS: We prospectively assessed pre-operative MR images of 58 patients (41 males, 17 females; age range 18–62 years) with arthroscopically confirmed meniscal tear. First, we evaluated the performance of the sagittal and thin-slice axial MR images for the diagnosis of meniscal tears. Second, we compared the correlation of tear types presumed from sagittal and axial MRI with arthroscopy and tear classification from axial MRI. Tears were classified on the sagittal plane and the axial plane separately. The diagnostic performance and tear classification were compared statistically with arthroscopy results, which is accepted as the standard of reference. RESULTS: 8 of 58 patients were removed from the study group because they had complex or degenerative tears. A total of 62 tears were detected with arthroscopy in 50 patients. On the sagittal images, sensitivity and specificity values were 90.62% and 70.37%, respectively, for medial meniscus tears and 72.73% and 77.14%, respectively, for lateral meniscus tears. The corresponding values for axial images were 97.30% and 84.00%, respectively, for medial meniscus tears and 95.65% and 80.50%, respectively, for lateral meniscus tears. There was no significant difference in tear classification between the arthroscopy results and the thin-slice axial PDW MRI results (p>0.05). CONCLUSION: thin-slice axial PDW MRI increases the sensitivity and specificity of meniscal tear detection and especially classification, which is important for surgical procedure decisions.